Constrained Amorphous Interphase and Mechanical Properties of Poly(3-Hydroxybutyrate-co-3-Hydroxyvalerate) - Righetti, Maria Cristina; Aliotta, Laura; Mallegni, Norma; Gazzano, Massimo; Passaglia, Elisa; Cinelli, Patrizia; Lazzeri, Andrea (Frontiers in Chemistry, 2019)
In the present study, for the first time the evolution of tensile mechanical properties of different poly(3-hydroxybutyrate-co-3-hydroxyvalerate) copolymers (PHBV8 and PHBV12, with 8 mol% and 12 mol% of HV co-units, respectively) as a function of the storage time at room temperature has been investigated in parallel with the quantification of the crystalline, mobile amorphous and rigid amorphous fractions. A comparison with the evolution of the crystalline and amorphous fractions in the homopolymer poly(3-hydroxybutyrate) (PHB) was also performed. For all the samples, the crystallinity was found to slightly increase during storage. In parallel the mobile amorphous fraction decreased markedly, with the result that a relevant increase in the RAF was detected. The RAF content in the copolymers was lower than that of PHB. For all the samples, the RAF formation during ageing was ascribed to the growth of secondary crystals in geometrically restricted areas. It has been demonstrated that the storage at Troom leads in PHB, PHBV8 and PHBV12 to a progressive increase in the total solid fraction (crystal phase + rigid amorphous fraction) and to a simultaneous physical ageing of the rigid amorphous fraction. The two different processes cannot be separated and distinguished, so that only the resulting effect on the mechanical properties was considered. The experimental elastic modulus of both PHBV8 and PHBV12 was found to increase regularly with the total solid fraction, as well as the tensile strength. Conversely, the elongation at break turned out to be an increasing function of the mobile amorphous fraction. The elastic moduli of the crystalline, mobile amorphous and rigid amorphous fractions of PHBV8 and PHBV12 were estimated by means of a three-phase modified Takayanagi’s model, to take into account also the contribution of the rigid amorphous fraction. The calculated values were found in agreement with theoretical expectations.